Emotion recognition deficits in children and adolescents with autism spectrum disorder: a comprehensive meta-analysis of accuracy and response time - Maryam Masoomi; Mahdieh Saeidi; Rommy Cedeno; Rommy Cedeno; Zahra Shahrivar; Mehdi Tehrani-Doost; Zerimar Ramirez; Divya Aishwarya Gandi; Sasidhar Gunturu; Sasidhar Gunturu (Frontiers in Child and Adolescent Psychiatry)
BackgroundAutism spectrum disorder is a neurodevelopmental condition characterized by persistent challenges in social communication and restricted, repetitive behaviors. Emotion recognition deficits are a core feature of ASD, impairing social functioning and quality of life. This meta-analysis evaluates emotion recognition accuracy and response time in individuals with autism spectrum disorder compared to neurotypical individuals and those with other neurodevelopmental disorders.MethodsThis systematic review with a meta-analysis was conducted following PRISMA guidelines. A comprehensive literature search across PubMed, Scopus, Cochrane Library, and Web of Science identified 13 studies published between 2006 and 2024. Data on emotion recognition accuracy and response times were synthesized using standardized mean differences in random-effects models. Heterogeneity was assessed using the I2 statistic, and sensitivity analyses were performed to ensure robustness.ResultsIndividuals with ASD exhibited significantly lower overall emotion recognition accuracy compared to TD individuals (SMD = −1.29, 95% CI: −2.20 to −0.39, p < 0.01) and NDDs (SMD = −0.89, 95% CI: −1.23 to −0.55, p = 0.02). Response times were significantly prolonged in ASD compared to TD individuals (SMD = 0.50, 95% CI: 0.36–0.63, p < 0.01) but not when compared to NDDs. Emotion-specific analyses did not consistently reveal significant differences across emotions (fear, anger, happiness, sadness, disgust, surprise), with substantial heterogeneity observed across studies (I2 > 50%).ConclusionsThis systematic review with a meta-analysis highlights significant impairments in emotion recognition accuracy and processing speed among individuals with autism spectrum disorder, particularly compared to neurotypical individuals. These findings underscore the importance of developing targeted interventions to address these deficits, which are foundational to improving social cognition and quality of life in autism spectrum disorder. Future research should prioritize standardized methodologies and explore cultural and contextual factors influencing emotion recognition abilities.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=627339, PROSPERO (CRD42024627339).